QUANTITY TAKE-OFF COMPARISON OF CONVENTIONAL AND BIM-BASED CUBICOST METHODS: A CASE STUDY OF SMPN 2 MEGALUH - M. Bayu Fernando Syahfikri; Dedi Enda; Roma Dearni (RADJA PUBLIKA, 2026)
Quantity Take-Off (QTO) is an essential process in construction projects as it directly influences cost estimation and project planning. Conventional quantity calculation methods often require more time and are prone to errors due to the manual interpretation of construction drawings. This study aims to compare the Quantity Take-Off results obtained using the conventional method and the Building Information Modeling (BIM) approach through Cubicost software in the construction project of SMPN 2 Megaluh. The BIM model was developed based on architectural, structural, and mechanical-electrical drawings using the Take-off for Architecture and Structure (TAS), Take-off for Reinforcement Bar (TRB), and Take-off for Mechanical, Electrical, and Plumbing (TME) modules. The quantities generated by Cubicost were then compared with those obtained through conventional calculations. The results indicate that most work categories produced relatively small deviations, demonstrating a good level of agreement between the two methods. The largest deviations in the TAS module were observed in ceiling works (15.93%) and earthworks (15.71%), while several work categories produced identical results. Quantity differences in the TRB and TME modules were generally influenced by modeling details, drawing interpretation, and calculation procedures. Overall, the BIM-based approach using Cubicost proved to be more efficient, integrated, and consistent in generating Quantity Take-Off data, making it a reliable alternative to conventional methods for construction quantity estimation.